The Relationship of Characteristics of Schizophrenic Clients with The Level of Self-Care Capability - Dora, Mechi Silvia; Arini, Larasuci (Indonesian Journal of Global Health Research, 2024)
This research aims to determine the relationship between the characteristics of schizophrenia clients and the level of self-care ability in the women's psychiatry ward at HB Saanin Mental Hospital, Padang. This type of analytical descriptive research with a research design using a cross sectional approach and sampling was carried out using a simple random sampling technique with a sample size of 39 respondents. The data collection tool was carried out using an observation sheet filled in by the researcher, and data processing was carried out using a computerized system. The research results obtained that most of the respondents (66.7%) were middle adults (31-60 years), Most of the respondents (56.4%) were married, Most of the respondents (64.1%) had a high level of education, Most Most of the respondents (59%) had the status of having been treated for a long time, the majority of respondents (48.7%) needed assistive devices to level their self-care abilities. There was a significant relationship between age and the level of self-care abilities (p value = 0.012 < 0.05), status marriage with the level of self-care ability (p value = 0.000 < 0.05), education with the level of self-care ability (p value = 0.000 < 0.05), and length of stay with the level of self-care ability in the women's psychiatric ward at HB Saanin Padang mental hospital ( p value = 0.000 < 0.05). For respondents, it should be possible to increase the client's ability to carry out self-care activities that have been given therapy by officers, so that the more they demonstrate the ability to carry out good self-care activities, the more it indicates that the client is approaching good awareness.